THE EFFECT OF EDUCATION AND HDI ON ECONOMIC GROWTH IN THE SPECIAL REGION OF YOGYAKARTA - Muhammad Zulfikar Yusuf; Nurrahmy Hidayati; Muhammad Ghafur Wibowo; Navi'ah Khusniati (Universitas Negeri Yogyakarta, 2022)
The human development index and education are one of the benchmarks for the success of economic development. Each country seeks to improve development achievements both monetary and non-monetary. This study aims to examine the effect of the Human Development Index and education as proxied by Average Years of Schooling, Expected Years of Schooling, Literacy Rate on economic growth. This study uses a panel data analysis method consisting of five districts/cities in the Province of the Special Region of Yogyakarta with an interval of 2015-2020. The data used is secondary data originating from the Central Statistics Agency. The results of this study indicate that HDI and AMH variables do not affect economic growth. While the variables RLS and HLS have a significant positive effect on economic growth. This research can be a reference for optimizing education and human development policies to increase economic growth in Yogyakarta.